Contemporary Islamophobia in Malaysia: Social Media, Legislation, and Cultural Tensions - Muhammad Muslim bin Rusli (Al-Jami'ah Research Centre, 2025)
Islamophobia in Malaysia remains a complex and under-explored phenomenon. This case especially occurs within the context of Muslim-majority society where both internal and external factors fuel hostility. Existing legal frameworks such as the Sedition Act and Penal Code inadequately address systemic and subtle Islamophobia, particularly in digital spaces. This study employs socio-political and legal analysis to examine how Islamophobia manifests in Malaysia’s context. The paper also explores the limitations of current policies. It argues for a dedicated anti-Islamophobia legal framework aligns with international human rights standards and advocates for multi-stakeholder cooperation, incorporating both civil and Syariah law systems alongside educational initiatives to counter prejudice and promote religious harmony. The findings suggest that only through nuance, inclusive strategies can Malaysia effectively confront Islamophobia while respecting freedom of expression and multicultural coexistence.[Islamofobia di Malaysia merupakan fenomena kompleks dan minim dieksplorasi. Kondisi ini utamanya dalam masyarakat mayoritas Muslim. yang dipengaruhi oleh faktor internal dan eksternal sebagai pemicu permusuhan. Kerangka hukum yang ada seperti Undang-Undang Hasutan dan Kitab Undang-Undang Hukum Pidana belum secara memadai menangani Islamofobia yang bersifat sistemik dan halus, khususnya dalam dunia digital. Studi ini menggunakan analisis sosial-politik dan hukum untuk mengkaji manifestasi Islamofobia dalam konteks Malaysia. Riset ini juga membahas keterbatasan kebijakan yang ada. Penelitian ini berargumen bahwa diperlukan kerangka hukum anti-Islamofobia yang menjunjung standar hak asasi manusia internasional, serta kerja sama antara sistem hukum sipil dan Syariah, disertai inisiatif pendidikan untuk melawan prasangka dan mendorong harmoni antaragama. Temuan menunjukkan bahwa hanya melalui strategi inklusif dan bernuansa Malaysia dapat menghadapi Islamofobia secara efektif sambil menghormati kebebasan berekspresi dan keberagaman budaya.]